The marriage of aesthetics and ethics (Critical Studies in German Idealism, 2015)
In The Marriage of Aesthetics and Ethics , fifteen authors reflect on the nature of friendship and love and on the complex relation between art and morality. Karl Verstrynge, Vincent Caudron, Anne Christine Habbard, and Walter Jaeschke draw from authors from Aristotle to Derrida, Montaigne to Kierkegaard, and Hegel to Blanchot to discuss friendship and love. Andreas Arndt, Paul Cobben, Paul Cruysberghs, Gerbert Faure, Simon Truwant, and Margherita Tonon focus on the connection between aesthetics and ethics in the works of Kant, Schiller, Hegel, Schleiermacher, Kierkegaard, Cassirer, and Adorno. Baldine Saint Girons, Stéphane Symons, Marlies De Munck, Stijn De Cauwer, and Willem Styfhals explore the connection between ethical and aesthetic issues in photography, film, music, literature, and the visual arts.